Internet in Costa Rican public libraries: its importance in bridging the digital divide - Rodríguez Chaves, Olga (2008)
Being the public library of free and open access, it constitutes one of the means of information and knowledge that offers opportunities to all members of the community and from where the rights to information, education, culture and recreation can be made effective. According to UNESCO, it is the responsibility of the public library to facilitate access to knowledge and information through the Internet, and thereby achieve its development and technological evolution. Currently, the Costa Rican public library is gradually entering the world of ICTs and is trying to integrate into the digital revolution to offer innovative, quality services and remain useful for citizens, while seeking to bridge the digital divide for those who have fewer opportunities.